A Single Nucleotide Polymorphism Translates into a Radical Amino Acid Substitution at the Ligand-Binding Site in Fasciola hepatica Carboxylesterase B - Miranda-Miranda, Estefan (2022)
Fasciola hepatica anthelmintic resistance may be associated with the catalytic activity of xenobiotic metabolizing enzymes. The gene expression of one of these enzymes, identified as carboxylesterase B (CestB), was previously described as inducible in adult parasites under anthelmintic treatment and exhibited a single nucleotide polymorphism at position 643 that translates into a radical amino acid substitution at position 215 from Glutamic acid to Lysine. Alphafold 3D models of both allelic sequences exhibited a significant affinity pocket rearrangement and different ligand-docking modeling results. Further bioinformatics analysis confirmed that the radical amino acid substitution is located at the ligand affinity site of the enzyme, affecting its affinity to serine hydrolase inhibitors and preferences for ester ligands. A field genotyping survey from parasite samples obtained from two developmental stages isolated from different host species from Argentina and Mexico exhibited a 37% allele distribution for 215E and a 29% allele distribution for 215K as well as a 34% E/K heterozygous distribution. No linkage to host species or geographic origin was found in any of the allele variants.